Determination of pyridoxine by means of an indicator diazo-test strip - Vera M Ostrovskaya; Alexander V Ivanov; Dmitry Yu Marchenko (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
Pyridoxine (vitamin B6) plays an important role in the body's metabolism. Reaction of azocoupling with diazoaryl compound underlies in a basis a known photometric method of its chemical analysis. This method is not selective. In the present work the test method of determination of the pyridoxine containing in a molecule hydroxyarylgroup, was proposed by them azocoupling with chromogenic indicator diazo test strip, consisting of a covalently fixed on cellulose reagent with functional diazoaryl group, attached to the cellulose carrier through 1,3-diphenoxypropane bridge. This test strip interaction with resulted in formation of cellulose tetradentate chelating agent, capable to enter the subsequent chromogenic reaction with copper (II) ion. Formation of blue-violet complex of azoderivative pyridoxine with copper was used for determination of the content of pyridoxine (vitamin B6) in a number of his pharmaceutical preparations.